2006
DOI: 10.1016/j.neuropsychologia.2005.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Intermanual transfer effects in sequential tactuomotor learning: Evidence for effector independent coding

Abstract: Results from our earlier brain imaging studies regarding motor learning have shown different areas activated during naive and practiced performance. When right handed participants moved a pen either with the dominant or non-dominant hand continuously through a cut-out maze as quickly and accurately as possible, practice resulted in decreased brain activity in right premotor and parietal areas as well as left cerebellum, while increased activity was found in the supplementary motor area (SMA). These lateralized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 54 publications
5
27
1
4
Order By: Relevance
“…Although intermanual transfer was observed previously (Halsband, 1992;Criscimagna-Hemminger et al, 2003;van Mier and Petersen, 2006;Wang et al, 2011), it was not found in the nonmirror task of the present study. This might have been because asymmetrical intermanual transfer occurred instead when using the symmetric mirror motor task (Kirsch and Hoffmann, 2010).…”
Section: Discussioncontrasting
confidence: 73%
“…Although intermanual transfer was observed previously (Halsband, 1992;Criscimagna-Hemminger et al, 2003;van Mier and Petersen, 2006;Wang et al, 2011), it was not found in the nonmirror task of the present study. This might have been because asymmetrical intermanual transfer occurred instead when using the symmetric mirror motor task (Kirsch and Hoffmann, 2010).…”
Section: Discussioncontrasting
confidence: 73%
“…Effector-independent movement coding has been observed in the case of transfer learning experiments (Grafton, Hazeltine, & Ivry, 1998;Swinnen et al, 2010;van Mier & Petersen, 2006). Our results show that an effector-independent representation is likewise used in haptic perception.…”
Section: Discussionsupporting
confidence: 65%
“…While some researches convey the absence of significant differences between genders 7,20,26 , other studies establish an interaction between age and gender 27,28 . A research from Santos 28 demonstrates that while in the youngest group female gender has got higher IMTL values than the male gender, in the oldest group the opposite was found.…”
Section: Gendermentioning
confidence: 99%
“…Some authors suggest that the process of transfer is symmetric (e.g. Stockel & Weigelt 6 van Mier & Petersen 7 ), others report a transfer behavior as being mainly asymmetric (e.g. Kumar & Mandal 8 ; Redding & Wallace 9 ).…”
Section: Introductionmentioning
confidence: 99%